The influence of Roger Corman in Richard Corben's The Fall of the House of Usher. Issue 1 (1st April 2013) - Saez de Adana, Francisco
This article presents a comparative analysis of the movie (directed by Roger Corman in 1960) and the comic-book version (drawn by Richard Corben in 1989 for Pacific Comics) of Edgar Allan Poe's The Fall of the House of Usher. Both adaptations can be considered unfaithful to the original tale. However, as M. L. Rosenblat affirms in his book about Poe and Cortazar, the originality of Poe is related to the creation of a new effect. This article studies how this effect is represented visually in Corman's work and how Corben uses some of the same visual ideas to revive this effect. Corman's work attempts to identify a relationship between Poe and Freud, affirming that they have the same concept of the unconscious. The difference between the conscious and the unconscious is shown by Corman in the opposition between the narrator of the story and the character of Roderick Usher as the director plays with the concept of on-camera (for the conscious) and off-camera (for the unconscious). The same idea is captured by Corben when he attempts to show this opposition between the two characters, including the physical resemblance of the narrator with Poe himself. This opposition between the conscious and the unconscious plays a crucial role in the way Corman develops the movie's scenarios (with two levels representing different states of mind) and places the camera. This article shows how Corben includes his own contributions but follows the principles introduced by Corman to create an oppressive atmosphere that reflects the effect created by Poe's tales. Other aspects examined in this article include the use of colour in both works to represent the melancholy, following the ideas presented by Yves Hersant in his essay about the colours of the melancholy, and the representation of the incestuous relationship between Roderick and Madeleine, which is similar in both works in the understanding of incest as an element of the American Gothic, as defined by Leslie Fiedler. Considering these aspects and following the idea presented by Linda Hutcheon in her book A Theory of Adaptation (2006), it can be affirmed that these adaptations share what can be called, in Benjaminian terms, a common aura.